Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Laptop Pada J-Bros Computer Padang - Ike Oktavia Desla; Khairil Aswan (Jurnal Bintang Manajemen, 2023)
This study aims to determine: 1. To determine the effect of physical evidence (real) on consumer satisfaction at J-Bros Computer Padang City; 2. To determine the effect of empathy (emphaty) on consumer satisfaction at J-Bros Computer Padang City; 3. To determine the effect of reliability (reliability) on consumer satisfaction at J-Bros Computer Padang City; 4. To determine the effect of responsiveness(responsiveness)on consumer satisfaction at J-Bros Computer Padang City; 5. To determine the effect of collateral (guarantee) on consumer satisfaction at J-Bros Computer Padang City; 6. To determine the effect of price (price) on consumer satisfaction at J-Bros Computer Padang City. The method used in this research is a quantitative method with a descriptive approach. The sample in this study was 80 respondents with a sampling technique using the number of samplespurposive sampling. The data analysis technique used is multiple linear regression analysis. The data analysis technique begins with the research instrument test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, and hypothesis testing. This study shows the results: 1) Physical Evidence (real) influential and significant to consumer satisfaction at J-Bros Computer Padang City; 2) Empathy has a positive effect on consumer satisfaction at J-Bros Computer in Padang City; 3) Reliability (reliability) has a positive and significant effect on customer satisfaction at J-Bros Computer Padang City; 4) Responsiveness (responsiveness) has a positive and significant effect on customer satisfaction at J-Bros Computer Padang City; 5) Guarantee (guarantee) has a positive and significant effect on customer satisfaction at J-Bros Computer Padang City; 6) Price (price) has a positive and significant effect on customer satisfaction at J-Bros Computer Padang City.